Effects of microtopographic patterns on plant growth and soil improvement in coastal wetlands of the Yellow River Delta - Zhang, Ke; Xia, Jiangbao; Su, Li; Gao, Fanglei; Cui, Qian; Xing, Xianshuang; Dong, Mingming; Li, Chuanrong (Frontiers in Plant Science, 2023)
To clarify the effects of microtopography on plant growth and soil water, salt and nutrient characteristics of saline soils in mudflats within muddy coastal zones and explore suitable microtopographic modifications, six microtopographic modification patterns, namely, S-shaped, stripe-shaped, pin-shaped, step-shaped, dense stripe-shaped and crescent-shaped patterns, were established in the coastal mudflats of the Yellow River Delta. The soil water, salt, ion, total carbon, total nitrogen, and total phosphorus contents and their ecological stoichiometric characteristics were measured and analyzed after the implementation of different microtopographic modification patterns, with bare mudflats as the control. The results showed that microtopographic modification significantly changed the soil water and salt contents and the soil total carbon, total nitrogen and total phosphorus contents. Compared with the bare ground, microtopographic transformation significantly promoted the growth of the pioneer plant Suaeda salsa, significantly increased the soil water and nutrient contents, and significantly decreased the soil salinity. The soil salinity was mainly reduced by Na+ and Cl- ions. The soil salinity and nutrient contents gradually decreased with increasing soil depth, indicating the occurrence of surface aggregation. Compared to that of the bare ground, the soil C/N was significantly lower and the N/P was significantly higher in the microtopographic treatments, and the overall performance suggested soil N limitation. The ions contained in the saline soil were dominated by Na+ and Cl-, followed by Mg2+ and SO42-, with lower contents of K+, Ca2+ and HCO3-. Among the six microtopography modification patterns, the crescent-shaped pattern best promoted vegetation restoration. This pattern was the most effective in reducing soil salinity, with a 98.53% reduction in soil salinity compared with that of bare ground, followed by the pin-shaped pattern. Compared with that in the bare ground samples, the nutrient content in the samples from the step-shaped modification increased by 23.27%; finally, the S-shaped, step-shaped and dense stripe-shaped patterns performed poorly in terms of plant restoration and soil improvement. It is suggested that a crescent-shaped pattern should be considered first when carrying out microtopographic transformation on the beaches of the Yellow River Delta, followed by stripe-shaped and pin-shaped patterns. The S-shape should not be adopted.